El educador, agente necesario de la construcción social - Valle López, Angela del (2008)
In the postmodern society the role of the school and the teacher is strongly conditionedby the social demands of each particular context. The continuous changecannot be stop as it depends on science and technology. It is urgent to understandthat in a human universe that is changing because the performers and their roleschange, the social dynamics and the views of the world change, the central roleof education is to be assumed knowing that in the present historical situation theteacher is the direct subject in the debate. In view of this, we raise the question onwhat is the role of the educator today. The new approaches and demands requirea new professional culture in accord with the educational institution. Education isin need of change on the ways to impart knowledge and the ways of learning; it isin need of competent educators who have a new concept of their own role.